Influence of agitation on the growth of tio2 nanotubes on the surface of commercially pure titanium discs - de Souza, Barbara Lois Mathias [UNESP]; Nakazato, Roberto Zenhei [UNESP]; Claro, Ana Paula Rosifini Alves [UNESP]; Escada, Ana Lúcia Do Amaral [UNESP] (FapUNIFESP (SciELO), 2021)
Current strategies in the design of biomaterials include altering the surface properties of the biomaterial to systematically direct cellular behavior. Titanium is the most prevalent material for use in implants due to its mechanical properties. Modifications to the titanium surface can optimize the osseointegration of an implant by modulating the immunosuppressive response, accelerating the healing process and reducing treatment time. The growth of TiO2 nanotubes through anodization can alter the surface properties of commercially pure titanium, allowing a better response when inserted into the human body. Objective of the present work was the growth of TiO2 nanotubes on the surface of commercially pure titanium discs and the reduction of anodization time, with agitation during anodic oxidation, voltage of 30V and electrolyte composed of 90-10% (v/v) ethyleneglycol-H2O and 1% NH4F (w/w). To determine the best agitation intensity, a time of 20 minutes was established. The agitation intensity was classified by the observation method, classified as weak, moderate and vigorous. To determine the best anodic oxidation time, moderate agitation intensity was estab-lished. The anodizing time should allow the structure to reorganize and increase the degree of self-organization, thus, times of 20, 30 and 40 minutes have been established. Then, the samples were subjected to calcination in an EDG muffle furnace with a heating rate of 5ºC/minute, maintained for 1 hour at 450ºC. The surface morphology was analyzed by scanning electron microscopy (SEM), contact angle and X-ray diffraction (XRD).
Influência da agitação no crescimento de nanotubos de tio2 na superfície de discos de titânio comercialmente puro
Keywords: Agitation; Anodization; Biomaterials; Titanium